The Influence Of Electronic Word Of Mouth And Brand Trust On Product Purchase Decisions Among Tokopedia Application Users - kadek Sadu Gunawan; Fridayana Yudiaatmaja (Journal of Management, Economic, and Accounting, 2026)
This study was conducted to determine how Electronic Word Of Mouth and Brand Trust influence Product Purchasing Decisions on Tokopedia platform users. This study was conducted on Tokopedia application users to determine the influence of Electronic Word Of Mouth and Brand Trust on Product Purchasing Decisions. The results of the study indicate that Electronic Word Of Mouth (X1) influences Product Purchasing Decisions (Y). Brand Trust (X2) influences Product Purchasing Decisions (Y). And Electronic Word Of Mouth (X1) and Brand Trust (X2) jointly influence Product Purchasing Decisions (Y). Information or messages contained in eWOM can be a reference for consumers in evaluating a product or brand. Brand trust is the consumer's point of view with the brand and the sense of trust in the brand, satisfaction, experience, and direct use that creates trust in a particular brand. Tokopedia application users in determining purchasing decisions on a product tend to look at product reviews and use personal experiences on a brand.